CONSUMMATE LOVE VALUED BY STERNBERG’S TRIANGULAR OF LOVE REFLECTED IN “SUNRISE IN HEAVEN” (2019) MOVIE: PSYCHOLOGICAL APPROACH - Elhamsyah, Galuh Virginia; Rudianto, Gaguk (BASIS (Bahasa dan Sastra Inggris), 2024)
Abstract This study aims to explain and analyze the phenomenon of love proposed by an expert Robert J Sternberg to the main characters in the film Sunrise in Heaven (2019). This research is a type of qualitative descriptive research, and the data source taken is the film Sunrise in Heaven (2019). This film is based on Jan Hurst's true-story novel entitled "His Sunrise, My Sunset," which she wrote herself. This story tells about Jan Nichols' love journey with her husband, Steve Hurst. The researcher found that the love story of the main characters, Steve and Jan, reflects the type of consummate love created by Robert J. Sternberg. Steve and Jan were able to represent the elements of Passion, Intimacy, and Decision/Commitment in their love journey. A love story that at first was not approved by Jan’s father, but with the strength of their love, they can prove that their love is eternal until they are parted by death. Keywords: Consummate love, Decision/Commitment, Intimacy, Passion, Triangular theory of love